2013
DOI: 10.1038/ng.2601
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of DEPDC5 cause autosomal dominant focal epilepsies

Abstract: The main familial focal epilepsies of childhood are autosomal dominant nocturnal frontal lobe epilepsy, familial temporal lobe epilepsy and familial focal epilepsy with variable foci. A frameshift mutation in the DEPDC5 (DEP domain containing protein 5) gene was identified in a family with focal epilepsy with variable foci, by linkage analysis and exome sequencing. Subsequent pyrosequencing of DEPDC5 in a cohort of 15 additional families with focal epilepsies revealed four nonsense and one missense mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(210 citation statements)
references
References 17 publications
6
200
1
3
Order By: Relevance
“…3). Of particular note, the first evidence for a genetic link came from inherited focal epilepsies, where loss-of-function mutations in the mammalian SEA1 gene (DEPDC5) have been associated with various forms of this disorder (Baulac, 2014;Dibbens et al, 2013;Ishida et al, 2013;Scheffer et al, 2014). Some of these mutations have been shown to disrupt DEPDC5-dependent inhibition of TORC1 (van Kranenburg et al, 2015).…”
Section: Deregulation Of Gator In Cancer and Other Diseasesmentioning
confidence: 99%
“…3). Of particular note, the first evidence for a genetic link came from inherited focal epilepsies, where loss-of-function mutations in the mammalian SEA1 gene (DEPDC5) have been associated with various forms of this disorder (Baulac, 2014;Dibbens et al, 2013;Ishida et al, 2013;Scheffer et al, 2014). Some of these mutations have been shown to disrupt DEPDC5-dependent inhibition of TORC1 (van Kranenburg et al, 2015).…”
Section: Deregulation Of Gator In Cancer and Other Diseasesmentioning
confidence: 99%
“…These findings suggest that GATOR1 is a tumor suppressor complex upstream of mTORC1. Two independent exome-sequencing analyses of familial focal epilepsy identified loss-of-function mutations in DEPDC5 [114,115], suggesting that hyperactive mTORC1 may cause epilepsy and mTORC1 inhibitors may be used to treat this disorder.…”
Section: Human Diseases Associated With Defects In Amino Acid Sensingmentioning
confidence: 99%
“…Affected individuals do not show cognitive deficits, although some family members exhibit intellectual disability. Recent studies have identified in some of these families mutations in Dishevelled, Egl-10 and Pleckstrin domain-containing protein, the function of which is still unclear, but it might be involved in membrane trafficking, G protein signaling and/or modulation of the mammalian target of rapamycin complex 1 (Table 1) [149][150][151]. Most mutations resulted in a truncated protein and are consistent with loss of function.…”
Section: Familial Focal Epilepsy With Variable Focimentioning
confidence: 86%